2017
DOI: 10.1007/s10903-017-0566-8
|View full text |Cite
|
Sign up to set email alerts
|

A Universal Health Care System? Unmet Need for Medical Care Among Regular and Irregular Immigrants in Italy

Abstract: Italy has a universal health care system that covers, in principle, the whole resident population, irrespective of citizenship and legal status. This study calculates the prevalence of unmet need for medical care among Italian citizens, regular and irregular immigrants and estimates logistic regression models to assess whether differences by citizenship and legal status hold true once adjusting for potential confounders. The analysis is based on two Surveys on Income and Living Conditions of Italian households… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
12
2
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 9 publications
(14 reference statements)
5
12
2
2
Order By: Relevance
“…Similar results were obtained for variables such as age [21,26,27,36], marital status [37], [40], educational status [26,39,41] and household income [28,42].…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…Similar results were obtained for variables such as age [21,26,27,36], marital status [37], [40], educational status [26,39,41] and household income [28,42].…”
Section: Discussionsupporting
confidence: 77%
“…In other studies related to health services not met in medical care, gender variable, which is one of the demographic features, was found to be a signi cant factor [38] but in this study, it was found that it wasn't signi cant factor. Similarly, birthplace and citizenship variables are among the variables that have no signi cant effect unlike other study results [36,39].…”
Section: Discussioncontrasting
confidence: 68%
See 1 more Smart Citation
“…Despite universal health coverage, previous studies have shown that in many countries there are inequities in unmet need for medical care between people of foreign background (PFB) and the general population. [1][2][3] Similar results have been reported in Finland 4,5 . The experiences of unjust treatment appear to be more common among immigrants and ethnic minorities in comparison to the general population in many countries 6,7 , including Finland 8 .…”
Section: Introductionsupporting
confidence: 86%
“…Perceived unjust treatment has also been linked to poorer self-rated health 8,20 which is a widely accepted predictor of both morbidity and mortality 23 . Those that report poor self-rated health or have existing chronic illnesses often also express greater need for medical care than others 3,24 .…”
Section: Introductionmentioning
confidence: 99%